2015
DOI: 10.1111/oik.02532
|View full text |Cite
|
Sign up to set email alerts
|

Motifs in the assembly of food web networks

Abstract: The assembly of local communities from regional pools is a multifaceted process that involves the confluence of interactions and environmental conditions at the local scale and biogeographic and evolutionary history at the regional scale. Understanding the relative influence of these factors on community structure has remained a challenge and mechanisms driving community assembly are often inferred from patterns of taxonomic, functional, and phylogenetic diversity. Moreover, community assembly is often viewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 60 publications
0
39
0
Order By: Relevance
“…A relatively new approach explores the network structure of multiple networks of the same type over large spatial extents (e.g., [166,172]). This approach has potential for identifying drivers of change in network structure, how species' roles change within networks over space and time [173], and the assembly of local networks from networks at continental and regional scales (a.k.a., metawebs; [174]). …”
Section: Discussionmentioning
confidence: 99%
“…A relatively new approach explores the network structure of multiple networks of the same type over large spatial extents (e.g., [166,172]). This approach has potential for identifying drivers of change in network structure, how species' roles change within networks over space and time [173], and the assembly of local networks from networks at continental and regional scales (a.k.a., metawebs; [174]). …”
Section: Discussionmentioning
confidence: 99%
“…) to network assembly (Baiser et al. ), stability (Allesina and Pascual , Borrelli et al. ), and persistence in food‐webs (Stouffer and Bascompte ).…”
Section: Benchmarking: Trusting Our Models Of Mechanismsmentioning
confidence: 99%
“…The ER model has been applied in ecology to address questions about the relationship between stability and complexity (May 1972) and the structure of genetic networks (Kauffman et al 2003). For example, randomized networks have been used to link motifs (Milo et al 2002) to network assembly (Baiser et al 2016), stability (Allesina and Pascual 2008, Borrelli et al 2015, and persistence in food-webs (Stouffer and Bascompte 2010).…”
Section: Benchmarking: Trusting Our Models Of Mechanismsmentioning
confidence: 99%
“…We computed all possible network motifs composed by 2-4 nodes and identified the motifs with high enrichment in each RT network constructed per differentiation pathway (Supplemental Figures S3-S5). Statistical significance (pvalue <0.01) of each motif occurrence in the RT networks was calculated by comparing to the frequency of the same motif in randomized networks (Milo et al 2002;Baiser et al 2015;Elhesha 260 and Kahveci 2016). The most frequent motifs with 2, 3 and 4 nodes in each differentiation pathway are shown in Figure 4B.…”
Section: Building Blocks Of Rt Network Are Motifs With Multiple Nodementioning
confidence: 99%
“…The analysis was limited to motifs of ≤ 4 nodes. First, because it has been shown that the fundamental regulatory 555 sub-network patterns consist of a small number of nodes networks (Baiser et al, 2015;Elhesha and Kahveci, 2016;Milo et al, 2002;Yeger-Lotem et al, 2004). Second, because the number of possible motif topologies grow exponentially with number of nodes making it impossible to test larger motif sizes.…”
mentioning
confidence: 99%